THE CORRELATION BETWEEN ANTIBIOTIC SENSITIVITY AND OUTCOME OF SEPSIS PATIENTS IN INTENSIVE CARE UNIT (ICU) AT DR. H. ABDUL MOELOEK HOSPITAL LAMPUNG PROVINCE 2018-2021 - Jaya Firmansyah; Ari Wahyuni; Maya Ganda Ratna; Novita Carolia (Medula, 2022)
Sepsis is a life-threatening condition of organ dysfunction due to dysregulation of the host response to infection. Antibiotic therapy is the main treatment for sepsis patients. The high rate of antibiotic resistance in the community is a serious problem in sepsis therapy that affects patient outcomes. The objective was to determine the relationship between antibiotic sensitivity and the outcome of sepsis patients in intensive care unit (ICU) RSUD Dr. H. Abdul Moeloek Lampung Province 2018-2021. The design of this research was observational analytic with cross sectional approach. Total sampling technique was used. Analysis of the data used was chi square test. The characteristics of sepsis patients were male patients (51.1%), elderly age group (43.2%), respiratory tract infection (28.4%), patients with comorbidities (51.1%), and the patient recovered (51.1%). The antibiotic profile showed that the most widely used antibiotic was ceftriaxone (36.4%), frequency of administration ≤2 times (65.9%), duration of administration ≤7 days (76.1%), and sensitive antibiotics (59.1%). Bivariate analysis showed that there was a significant correlation between antibiotic sensitivity and outcome of sepsis patients in the intensive care unit (ICU) RSUD Dr. H. Abdul Moeloek Lampung Province in 2018-2021 with a p value of 0.01 (<0.05).